KEANEKARAGAMAN DAN POTENSI ROTAN DI TAMAN WISATA ALAM BULUH CINA DESA BULUH CINA KABUPATEN KAMPAR - Alpino Alpino; Defri Yoza; Muhammad Mardhiansyah (JURNAL ILMU-ILMU KEHUTANAN, 2020)
Rattan is a non-timber forest product that had very high economic value. This study aims to identify the diversity of rattan species and determine the pattern of rattan distribution found in Buluh Cina Nature Tourism Park, Buluh Cina Village, Kampar District. The benefits of this research were as a source of knowledge and information about the diversity of rattan species in Buluh Cina Nature Tourism Park. The types of data collected in this study were primary data and secondary data. The stages of this research was the position of the track or transect in the field determined using the Purposive Sampling Method. Data analysis in this study was descriptive. The diversity of rattan species in the Buluh Cina Nature Tourism Park, includes six types of rattan, namely Rattan Getah (Daemonorops angistofolia), Rattan Water Sago (Calamus axillaris), Rattan Sago Air (Calamus caesius), Rattan Cacing (Calamus cilliaris), Rattan Cimoti (Calamus sp) and Rattan Tunggal (Calamus sp), with the value of  diversity index 1.03 was clasified as low. The pattern of distribution of rattan was grouped (aggregate), this is because the value of Id on each observation line more than 1 species.